Delivery vehicle effects on bone regeneration and heterotopic ossification induced by high dose BMP-2. (February 2017) - Krishnan, Laxminarayanan; Priddy, Lauren B.; Esancy, Camden; Klosterhoff, Brett S.; Stevens, Hazel Y.; Tran, Lisa; Guldberg, Robert E.
Graphical abstract: Abstract: Bone morphogenetic protein-2 (BMP-2), delivered on absorbable collagen sponge, is frequently used to treat bone defects. However, supraphysiological BMP-2 doses are common and often associated with complications such as heterotopic ossification and inflammation, causing pain and impaired mobility. This has prompted investigations into strategies to spatially control bone regeneration, for example growth factor delivery in appropriate scaffolds. Our objective was to investigate the spatiotemporal effects of high dose BMP-2 on bone regeneration as a function of the delivery vehicle. We hypothesized that an alginate delivery system would spatially restrict bone formation compared to a collagen sponge delivery system. In vitro, BMP-2 release was accelerated from collagen sponge compared to alginate constructs. In vivo, bone regeneration was evaluated over 12 weeks in critically sized rat femoral segmental defects treated with 30 μg rhBMP-2 in alginate hydrogel or collagen sponge, surrounded by perforated nanofiber meshes. Total bone volume, calculated from micro-CT reconstructions, was higher in the alginate group at 12 weeks. Though bone volume within the central defect region was greater in the alginate group at 8 and 12 weeks, heterotopic bone volume was similar between groups. Likewise, mechanical properties from ex vivo torsional testing were comparable between groups. Histology corroborated these findings and revealed heterotopic mineralization at 2 weeks post-surgery in both groups. Overall, this study recapitulated the heterotopic ossification associated with high dose BMP-2 delivery, and demonstrated that the amount and spatial pattern of bone formation was dependent on the delivery matrix. Statement of Significance: Alginate hydrogel-based BMP-2 delivery has induced better spatiotemporal bone regeneration in animals, compared to clinically used collagen sponge, at lower BMP-2 doses. Lack of clear dose-response relationships for BMP-2 vis-à-vis bone regeneration has contributed to the use of higher doses clinically. We investigated the potential of the alginate system, with comparatively favorable BMP-2 release-kinetics, to reduce heterotopic ossification and promote bone regeneration, when used with a high BMP-2 dose. While defect mineralization improved with alginate hydrogel, the initial high-release phase and likely early tissue exposure to BMP-2 appeared sufficient to induce heterotopic ossification. The characterization presented here should provide the framework for future evaluations of strategies to optimize bone formation and minimize adverse effects of high dose BMP-2 therapy.